On the move to meaningful internet systems : OTM 2019 workshops : Confederated International Workshops: EI2N, FBM, ICSP, Meta4eS and SIAnA 2019, Rhodes, Greece, October 21-25, 2019, Revised Selected Papers /: OTM 2019 workshops : Confederated International Workshops: EI2N, FBM, ICSP, Meta4eS and SIAnA 2019, Rhodes, Greece, October 21-25, 2019, Revised Selected Papers. (2020) - Unknown
No abstract available